2012
DOI: 10.5535/arm.2012.36.5.681
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Initial Extracorporeal Shock Wave Therapy on the Newly Diagnosed Lateral or Medial Epicondylitis

Abstract: ObjectiveTo evaluate the effectiveness of initial extracorporeal shock wave therapy (ESWT) for patients newly diagnosed with lateral or medial epicondylitis, compared to local steroid injection.MethodAn analysis was conducted of twenty-two patients who were newly confirmed as lateral or medial epicondylitis through medical history and physical examination. The ESWT group (n=12) was treated once a week for 3 weeks using low energy (0.06-0.12 mJ/mm2, 2,000 shocks), while the local steroid injection group (n=10) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 25 publications
2
33
0
7
Order By: Relevance
“…A multicenter, randomized, placebo-controlled single-blind study by Haake et al found that ESWT under local anesthesia was no more effective than placebo at 12 weeks (25.8% vs. 25.4% success rates) [22]. Similarly, Lee et al [35] found that ESWT was no more effective than corticosteroid injection for newly diagnosed LE and medical epicondylitis immediately after treatment and at 8-week follow-up. However, longer term follow-up may reveal differences not observed in the early posttreatment stage.…”
Section: Discussionmentioning
confidence: 99%
“…A multicenter, randomized, placebo-controlled single-blind study by Haake et al found that ESWT under local anesthesia was no more effective than placebo at 12 weeks (25.8% vs. 25.4% success rates) [22]. Similarly, Lee et al [35] found that ESWT was no more effective than corticosteroid injection for newly diagnosed LE and medical epicondylitis immediately after treatment and at 8-week follow-up. However, longer term follow-up may reveal differences not observed in the early posttreatment stage.…”
Section: Discussionmentioning
confidence: 99%
“…Lee ve ark. [31] ESWT'nin lokal steroid enjeksiyonu kadar etkili olduğunu ileri sürerken, Devrimsel ve ark. [32] ESWT'nin lazer tedavisine kıyasla daha etkili olduğunu bildirmişlerdir.…”
Section: Discussionunclassified
“…Its exact mechanism of action is unclear. Lee et al 23 found that epicondylitis patients treated with ESWT improved as much as patients treated with local steroid injection at 8 weeks post treatment. However, a Cochrane review that analyzed nine studies of more than 1000 lateral epicondylitis patients treated with ESWT did not demonstrate a statistically significant benefit with ESWT.…”
Section: Electrophysical Modalitiesmentioning
confidence: 97%